Vulnerability Index Assessment for Mapping Ground Movements Using the Microtremor Method as Geological Hazard Mitigation - Adi Susilo; Siti Zulaikah; A. Fauzi Pohan; M. Fathur Rouf Hasan; Farizky Hisyam; Siti Rohmah; M. Aryono Adhi (Salehan Institute of Higher Education, 2024)
Various geological disasters, such as landslides and ground movements, occur annually in Srimulyo Village, Malang District, with varying levels of damage. Ground movements can affect structures built above, causing sinking, cracking, and collapse. Research into landslides and ground movements triggered by vibrations is generally conducted using the microtremor method, which has proven effective. This study uses the microtremor method to map the soil condition that is potentially prone to movement or landslides based on the observed soil vulnerability index. Data was collected using a TDL 303s Digital Portable Seismograph instrument; the measurement points were established in the form of a grid distributed across the research area, with a recording duration of approximately 45 minutes at each point. The analysis technique utilizes the Horizontal Vertical Spectrum Ratio (HVSR) based on the Fast Fourier Transform (FFT) principle. The study’s results found that the research location’s seismic vulnerability index varies between 6.5 and 16.5. Areas with high seismic vulnerability index values, specifically those with Kg>11.5, are scattered on the west, south, and southeast sides of the research location. Based on field observations, these areas are dominated by relatively thick sediment layers, leading to lower dominant frequency values and higher amplification values; consequently, the seismic vulnerability index in the southern region is also high. Doi: 10.28991/CEJ-2024-010-05-017 Full Text: PDF